Integration of Multidisciplinary Approaches in the Criminal Justice System: A Study of the Handling of Gender-Based Crime - Ahmad Abrari; Siti Aisyah (PT. Anagata Sembagi Education, 2025)
Gender-based crimes, such as sexual violence, domestic violence, and exploitation of women and children, are complex issues that require multidisciplinary handling. In Indonesia, although Law Number 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS) has been adopted as a step forward, its implementation still faces various obstacles, such as limited understanding of law enforcement officials regarding gender issues and lack of collaboration with other disciplines such as psychology and sociology. The dominance of patriarchal culture and a judicial system focused on formal legal procedures often ignores the social and psychological needs of victims. Therefore, a multidisciplinary approach involving various professions, such as psychologists, social workers, and human rights activists, is needed to ensure the protection and recovery of victims in a comprehensive manner. A criminal justice system that is more responsive to the needs of victims can be achieved by improving coordination between agencies and strengthening the capacity of law enforcement officials through gender-based training. This study uses descriptive-analytical methods to evaluate the challenges and opportunities of implementing this approach, relying on secondary data from regulations, government agency reports and NGOs. It is hoped that the results of this study can provide recommendations to strengthen judicial policies and practices that are fairer and more inclusive